Recopier, interpréter, transposer : la création romantique face aux défis de la civilisation moderne - Wojda, Aleksandra (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2019)
The article is devoted to relationships between the transformations that take place in the Romantic aesthetics and artistic practice, and the media revolution that co-shaped the art of the first decades of the nineteenth century. The author analyses in particular the way in which the expansion of print – resulting from the evolution of the contemporary technologies that allowed for the reproduction of texts, as well as scores and paintings – influences the Romantic models of understanding of such issues as the relation between the original and the copy, between the work and its interpretation, between its record and execution. The endpoint for the proposed study is the thesis that, in the face of the growing danger of standardization in art, provoking in the Romantics a peculiar “fear of reproduction”, the contemporary artists try to realise a new concept of medium as a personalized and individualised instance, creatively affecting the shape of their works. This, in turn, favours and supports the artistic potential of the mediation process itself, which T. Gautier will describe as the transposition of the arts.